PENGARUH PEMBERIAN PUPUK CAIR TERHADAP PENYAKIT LAYU BAKTERI (Ralstonia solanacearum) PADA TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Aulya Retno Setyari; Luqman Qurata Aini; Abdul Latief Abadi (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
ABSTRACTTomato (Lycopersicum esculentum) is an annual fruit plant that can be planted on high or low-land. Tomato has many beneficial vitamins and minerals to fulfillhuman body need for health. Tomato contains vitamins and minerals in amount of 30 calories, vitamin C 40 mg, vitamin A 1.500 SI, zinc, and calcium. Main cause of areal cultivation reduction are land degradation, erosions, and high intensity of bacterial wilt disease Ralstonia solanacearum that was the main consequences of perpetually tomato cultivation. Liquid fertilizer application gives some alternate way to control bacterial wilt disease Ralstonia solanacearum that also known as pathogen soil infection. Liquid fertilizer that used in this research is made from amino acid residual process. Purpose of this research is to observe the effect of liquid fertilizer giving that applied to the soil and leaves towards tomato plant growth. Result of this research shows that liquid root or foliar fertilizer applicationeffects significantly on plant height and number of leaf parameters of alltreatments and all observation time.Keywords: tomato, Ralstonia solanacearum, liquid fertilizer